Governance and Regulation of Power Pools and System Operators An International Comparison (Washington World Bank Publications, 1997)
Annotation World Bank Technical Paper No. 382. This technical paper compares and contrasts the governance and regulation of "new style" power pools in Australia, Canada, Norway, Sweden, and the United Kingdom. These trading markets in electricity com modities and services are explored in various ways. The authors review the basic governance models, compare decisionmakers in the industry, examine market surveillance methods used, and explore the role of government and the regulator. The paper emphasizes the lessons that can be learned from international experiences.
Annotation World Bank Technical Paper No. 382.This technical paper compares and contrasts the governance and regulation of new style power pools in Australia, Canada, Norway, Sweden, and the United Kingdom. These trading markets in electricity commod ities and services are explored in various ways. The authors review the basic governance models, compare decisionmakers in the industry, examine market surveillance methods used, and explore the role of government and the regulator. The paper emphasizes the lessons that can be learned from international experiences.
Scholarly & Professional
Keywords: World Bank